ANALYSIS OF THE ECONOMIC IMPACTS OF SUSTAINABLE DEVELOPMENT ON ECONOMIC GROWTH IN DEVELOPING COUNTRIES: APPLIED STUDY IN A SAMPLE OF DEVELOPING COUNTRIES IN ASIA, AFRICA AND SOUTH AMERICA (World Economics and Finance Bulletin, 2025)
This research aims to analyze the economic impacts of sustainable development initiatives on economic growth rates in developing countries. The study relied on a quantitative analytical approach using secondary data from UN and World Bank reports, while analyzing development trends and their impact on GDP. The research community represents all developing countries that have highly reliable data on indicators of sustainable development and economic growth during the period (2015-2023), according to the classifications of the World Bank and the United Nations. As for the research sample, it was selected intentionally, where ten developing countries representing appropriate geographical and economic diversity were selected, while ensuring the availability of the required data for statistical analysis, namely: Egypt, Nigeria, Ethiopia, India, Indonesia, Pakistan, Brazil, Argentina, Kenya and the Philippines. The results showed a moderate positive relationship between the application of sustainable development standards and economic growth, with significant variation between countries according to public policies and the extent to which the SDGs are integrated into their economic strategies. The study recommended strengthening institutional policies, increasing investment in green technology, and achieving transparency to ensure the effectiveness of sustainable development in promoting economic growth.
Keywords: effectiveness; initiatives; economic growth